Mapping metacognitive awareness of Chinese language learners - Diana Nur Sholihah; Zakiyah Arifa; Kartika Ratnasari; Nur Ila Ifawati (Journal of Education and Learning (EduLearn), 2021)
The role of metacognitive awareness on language teaching and learning have been confirmed by several studies, but the discussions of this topic in Chinese as foreign language are limited. The aim of the present research was to map metacognitive awareness profile of Chinese language learners. Total respondent of this research was 80 Chinese language learners (38 males and 42 females) which comprise secondary students. Convenience sampling technique was employed to select the respondents. Meanwhile, the metacognitive awareness data were collected utilizing Junior Metacognitive Inventory. The obtained data were analyzed using descriptive statistic. Mann-Whitney U Test was employed to investigate the significance differences of metacognitive awareness between male and female. The findings showed that 46.25% of Chinese Language Learners have a good metacognitive knowledge, 28.75% fair, 20% very good, 3.75% poor, and 1.25% very lacking. The finding also showed that 40% students have good metacognitive regulation, 36.25% fair, 15% very good, 7.50% poor, and 1.25% very lacking. In addition, between male and female students have no significant difference in knowledge of cognition. On the contrary, regulation of cognition female learners (Mdn= 32.50) significantly (U= 551.000, p more than 0.05) better compared to male (Mdn= 30).